The Workload of Health Workers in The Medical Record Unit During the Covid-19 Pandemic - Riska Rosita; Devi Prasetyo Ramadani; Diyan Nurhaini; Ratih Kusumaningtyas; Indra Agung Yudistiro; Harjanti (Proceeding of International Conference on Science, Health, And Technology, 2021)
The medical record unit is the holder of data for all patients so that the performance of medical record workers supports the quality of health services. The problem that occurs in the Community Health centers at Sawit Indonesia, Medical Record Unit is the limited number of workers so that the service to patients tends to belong. The number of patient visits during the Covid-19 pandemic reached 80-100 people/day. The purpose of this study was to analyze the workload of medical record unit workers. The research method used is qualitative with a descriptive research design. Data collection was carried out using observation and interviews. The results showed that: (1) registration workers were carried out by nurses, who served patient registration as well as assisting doctors in providing medication to patients and operating ambulances when needed, as a result, workers experienced work fatigue; (2) analyzing-reporting workers concurrently serve as cashiers, resulting in human errors, inaccurate data and inability to finish on time; and (3) filing workers are carried out by midwives who also provide medical treatment to patients so that the provision of medical record documents is delayed. Workers complain about fatigue, feeling dizzy, drowsy at work, loss of concentration, etc. Researchers suggest that Community Health centers at Sawit district, prepare job descriptions for workers so that the medical record unit can be carried out according to its function.